تعليم مهارة القراءة للناطقين بغيرها - Aqif Khilmia (UIN Fatmawati Sukarno Bengkulu, 2020)
AbstractReading is considered one of the most important acquired skills that achieve success and enjoyment for every individual during his life, on the grounds that reading is an integral part of personal and professional life and is the key to the gates of various sciences and knowledge. Reading skill is not enough with the student's intelligence, but rather is concerned with the presence of external and internal factors that encourage reading. Reading is the main source for learning the Arabic language and requires special and varied training. The teacher should pay attention to the steps of teaching the skill of reading according to the desired objectives. Teaching the skill of reading to non-native speakers requires special steps between the two types of intensive reading and the extended reading chosen by the teacher in education. And the reading test to reveal the level of the learners so that the problem of weakness of the students appears and the teacher can direct the student to an appropriate study program.